VALIDITY OF BIOLOGY STUDENT WORKSHEETS IN ELECTRONIC FORM BASED ON PROBLEM BASED LEARNING (PBL) - Noorhidayati Noorhidayati; Rabiatul Jannah; Maulana Khalid Riefani (ATRIUM PENDIDIKAN BIOLOGI, 2021)
Teachers play an important role in learning planning so that knowledge can be conveyed properly to students. The use of effective and interesting teaching materials, especially for the concept of Ecology which has a broad material coverage, can help students achieve the expected learning goals, one of which is the Electronic Student Worksheet. This study aims to describe the validity of the results of the development of the Electronic Biology Student Worksheet for Grade X High School Ecology Concepts Based on Problem Based Learning. This research is a research and development with a 4D model which is limited only to the Develop stage. The validity of Electronic Student Worksheet is seen based on the suitability test and feasibility test. The results of the suitability test obtained are with an average score of 4.50 which means that Electronic Student Worksheet is very suitable, and the results of the feasibility test which have an average score of 4.58 which means that Electronic Student Worksheet is very technically feasible to be used in learning.